The World of Cocos Malay Music and Dance:: A Documentary Film on Performing Arts in the Cocos (Keeling) Islands (Journal of Music Research Online, 2022)
The Cocos (Keeling) Islands, located halfway between Perth and Sri Lanka and part of Australia’s Indian Ocean Territories, are home to around 400 Cocos Malays and 150 others. Uninhabited until 1826, the islands became a coconut plantation controlled by the Scottish Clunies-Ross family and worked by Malay labourers from 1827 until 1978. In this isolated community there arose a unique and distinctive set of cultural practices, which drew from Malay, Javanese, and (some) Scottish influences. The rhythms of Cocos Malay life involve regular musicking and Islamic religious ritual: on specific occasions, including the week-long celebrations following Hari Raya (Eid al- Fitr), the birthday of the Prophet (Maulud Nabi), and weddings, the community comes together for festive public performances. This film and article present an ethnomusicological survey of Cocos Malay music and dance, based on fieldwork conducted in 2015 and 2016 during the festivities for Hari Raya. Among the genres presented and discussed are: zikir (remembrance of the Prophet), joget (popular Malaysian dance), nasyid (devotional songs), Scottish reels with Scottish dance music, traditional Cocos Malay dance with biola (violin), silat (a martial art), rudat (seated dance) with percussion, and bangsawan (popular theatre). Interviews explore the Cocos Malay biola tradition and projects for its revitalisation, and memories of music and dance for the Nuyar (New Year’s Eve) party that was held in the house of the Clunies-Ross family until the 1990s. The history and modern-day practice of Scottish dancing within this Malay Muslim community form a major focus of the narrative.